Structural, optical and XPS study of thermal evaporated In2O3 thin films. (14th August 2017) - Reddy, I Neelakanta; Venkata Reddy, Ch; Cho, Migyung; Shim, Jaesool; Kim, Dongseob
Abstract: The nanostructured In2 O3 thin films were deposited on Si n-type (1 0 0) substrates by reactive thermal evaporation. The structural, morphological, and oxidation states of the films were investigated using x-ray diffraction, scanning electron microscopy, atomic force microscopy, and x-ray photoelectron spectroscopy. The optical properties of the films were analyzed by UV–vis spectroscopy, Raman spectroscopy, and photoluminescence spectroscopy. The deposited films showed c-In2 O3 crystalline nanostructures with a preferred diffraction peak of (2 2 2). The truncated icosahedron shape's morphology with a transmittance of 85% was observed in the In2 O3 thin films. All the deposited indium oxide films have 3+ oxidation states.